2017
DOI: 10.17826/cutf.325568
|View full text |Cite
|
Sign up to set email alerts
|

Akut gastroenterit salgınının mikrobiyolojik değerlendirmesi

Abstract: ÖzPurpose: Acute gastroenteritis is one of the most important causes of morbidity and mortality especially in children. In water-borne outbreaks, more than one infectious agent may act as the cause of the disease due to contamination of water with feces. Material and Methods: We evaluated 440 patients who applied to Şırnak State Hospital Emergency Service in two weeks. Their complaints were; vomiting, abdominal pain and diarrhea and were pre-diagnosed as gastroentiritis. Fresh stool samples were examined by na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Through laboratory investigations, it was found that infection with Entamoeba histolytica results in leukocytosis [ 80 , 81 , 84 , 85 ], elevation of CRP [ 74 , 78 , 79 , 80 , 84 , 85 ], elevation of ESR [ 81 ], elevation of serum alkaline phosphatase, and serum transaminase levels [ 81 , 86 ]. Eating unwashed or raw vegetables [ 86 , 87 , 88 , 89 ] and poor water hygiene [ 82 , 90 , 91 ] were identified to increase the risk of Entamoeba histolytica infection.…”
Section: Causative Agents Of Agementioning
confidence: 99%
“…Through laboratory investigations, it was found that infection with Entamoeba histolytica results in leukocytosis [ 80 , 81 , 84 , 85 ], elevation of CRP [ 74 , 78 , 79 , 80 , 84 , 85 ], elevation of ESR [ 81 ], elevation of serum alkaline phosphatase, and serum transaminase levels [ 81 , 86 ]. Eating unwashed or raw vegetables [ 86 , 87 , 88 , 89 ] and poor water hygiene [ 82 , 90 , 91 ] were identified to increase the risk of Entamoeba histolytica infection.…”
Section: Causative Agents Of Agementioning
confidence: 99%